2004
DOI: 10.1016/j.ydbio.2004.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional signaling mediated by ephrin-B2 and EphB2 controls urorectal development

Abstract: Incomplete urethral tubularization (hypospadias) and anorectal abnormalities are two common and poorly understood birth defects that affect the extreme caudal midline of the human embryo. We now show that cell surface molecules essential for proper axon pathfinding in the developing nervous system, namely ephrin-B2 and the ephrin receptors EphB2 and EphB3, also play major roles in cell adhesion events that tubularize the urethra and partition the urinary and alimentary tracts. Mice carrying mutations which dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
225
2
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 208 publications
(245 citation statements)
references
References 60 publications
17
225
2
1
Order By: Relevance
“…In contrast, the Efnb2 lacZ/lacZ homozygous mice manifest severe anorectal malformations, with high imperforate anus in the males and persistent cloaca in females. These data, combined with the noted hypospadias in the male EphB2 and EphB3 compound mutant mice, suggested that B-subclass signaling plays a major role in early murine development of the urogenital and anorectal structures (24), perhaps due to altered adhesion/ repulsion signals between the embryonic tissues that express these genes. Thus far, no human disease has been associated with EFNB2 mutations, but, based on the mouse data, the gene appeared to be an excellent candidate gene to screen in humans with persistent cloaca.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In contrast, the Efnb2 lacZ/lacZ homozygous mice manifest severe anorectal malformations, with high imperforate anus in the males and persistent cloaca in females. These data, combined with the noted hypospadias in the male EphB2 and EphB3 compound mutant mice, suggested that B-subclass signaling plays a major role in early murine development of the urogenital and anorectal structures (24), perhaps due to altered adhesion/ repulsion signals between the embryonic tissues that express these genes. Thus far, no human disease has been associated with EFNB2 mutations, but, based on the mouse data, the gene appeared to be an excellent candidate gene to screen in humans with persistent cloaca.…”
Section: Discussionmentioning
confidence: 90%
“…In mutant Bsubclass Eph or Efn mice was identified an additional role during urogenital and anorectal development. Efnb2 is expressed in the normal urogenital sinus and cloacal epithelium of mice, while the EphB2 receptor is predominantly expressed in the adjacent mesoderm of the urorectal septum that migrated towards the caudal midline during septation (24,40). Male mice with Efnb2 lacZ/+ exhibited hypospadias, a midline birth defect of the penile urethra, and delayed closure of the perineum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, although in principle ephrinB2-PDZ interactions could affect ephrinB2 trafficking and membrane targeting (Urena et al, 1999;Altschuler et al, 2003) and thereby indirectly influence EphB receptor activation, the overall health of ephrinB2 ⌬V/⌬V animals and the successful apical epithelial targeting of unbound ephrinB2 ⌬V protein in pseudoglandular stage lung (G.W. and R.K., unpublished observations) suggests that substantial signaling downstream of EphB receptors is preserved in this allele (see also discussion in Cowan et al, 2004;Dravis et al, 2004;Makinen et al, 2005). Finally, it should be pointed out that there is mounting evidence that ephrinBs can modulate other signaling pathways independently of Eph receptors (Foo et al, 2006;Lee et al, 2006) and that the repertoire of PDZ domain containing proteins bound to ephrinB ligands could change in the presence versus the absence of stimulating receptor (Torres et al, 1998;Bruckner et al, 1999;Palmer et al, 2002).…”
Section: How Does Loss Of a Pdz Binding Site On Ephrinb2 Affect The Ementioning
confidence: 99%